(untitled) (Global Journal of Human-Social Science, 2024)
In this article, the author presents the characteristics and conceptual criteria that should identify a femicide according to the original conception of Femicide -or Feminicide-of the English term Femicide, first developed by the feminist Diana Russell. First, the author contrasts the original conceptualization of femicide and the technical definition proposed by the legislator in the Bolivian Penal Code on the classification of the crime of femicide and then makes a critical analysis of it. Second, he states that the concept of femicide -or feminicide-alludes to specific criteria, for example, the misogynist murder of a woman because of her gender, simply because she is a woman. Third, the author analyzes the mental state test and its conceptualization. Fourthly, he analyzes the systems of valuation of evidence. Likewise, he analyzes the system of sound criticism as a corrective criterion of justification of the judicial decision. Finally, he analyzes the evaluation of evidence and the evidential reasoning to which the independent and impartial judge or court must adjust.